Cell-Specific Aptamers as Emerging Therapeutics - Cindy Meyer; Ulrich Hahn; Andrea Rentmeister (Journal of Nucleic Acids)
Aptamers are short nucleic acids that bind to defined targets with high affinity and specificity. The first aptamers have been selected about two decades ago by an in vitro process named SELEX (systematic evolution of ligands by exponential enrichment). Since then, numerous aptamers with specificities for a variety of targets from small molecules to proteins or even whole cells have been selected. Their applications range from biosensing and diagnostics to therapy and target-oriented drug delivery. More recently, selections using complex targets such as live cells have become feasible. This paper summarizes progress in cell-SELEX techniques and highlights recent developments, particularly in the field of medically relevant aptamers with a focus on therapeutic and drug-delivery applications.